Pengaruh Panjang Api Dan Sudut Injeksi Terhadap Produktivitas Mesin DC Thermal Plasma Dalam Pembuatan Nano Partikel Alumina - Indra Surya Iwanata; Gaguk Jatisukamto; Muhammad Dimyati Nashrullah; Mahros Darsin; Ahmad Syuhri (Jurusan Teknik Mesin, 2022)
Nanoparticles are particles that have a size of nm and a size range of 1-100 nano. These particles are formed by the DC Thermal Plasma method. This study utilizes a 70 ampere DC Plasma cutting machine as a plasma flame. The combustion process is carried out in a reactor tube, and the material processed is Aluminum powder (Al) with a purity of 92.5%. The input mass of Aluminum powder is injected at 5gram. Burning process (15 seconds). The particles attached to the reactor wall are sucked in with the help of a vacuum pump then collected on the filter tube. The material is measured by mass using a digital scale. Analysis of the data used is using the Taguci L27 method. The parameters used in this study are injection angle with 3 variations (45 °, 60 °, 90 °) and fire length with 3 variations (2.31 cm; 3.87 cm; 4.28 cm). The contribution of machining parameters in the manufacture of alumina nanoparticles is significant, namely the injection angle parameter has a contribution of 37% and a fire length parameter of 4.2%. The results of the study are generally influenced by the injection angle. The optimum injection angle is 45 ° with an average of 3.56 grams and the least productivity is the injection angle parameter 90 ° which is equal to 2.17 grams The conclusion of the study is that the greater the material injection bend angle the less productivity of DC Thermal Plasma devices as well vice versa.